Analysis of Students' Difficulties in Solving Mathematics Problems in Grade 4 Elementary School - Syaf, Ahmad; Fauzi, Azra; Ramdhani, Lisda (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The aim of this study is to analyze the difficulties faced by fourth-grade students in solving mathematical problem-solving tasks based on Polya’s stages: understanding the problem, planning a strategy, implementing the plan, and evaluating the results. This research adopts a descriptive qualitative approach with four fourth-grade students at SDN Lido, Bima Regency, as subjects. Data were collected through observation, written tests, and interviews with the teacher. The findings indicate that students struggle at each stage of problem-solving, particularly in understanding the problem and selecting appropriate strategies. Factors such as lack of conceptual understanding, accuracy in calculations, and limited habit of evaluating answers contribute to these difficulties. These findings suggest the need for a more structured instructional approach and a supportive learning environment to enhance students' problem-solving skills.